Industrial IoT for architects and engineers : architecting secure, robust, and scalable industrial IoT solutions with AWS /: architecting secure, robust, and scalable industrial IoT solutions with AWS. (2023) - Bernal, Joey; Sridhar, Bharath
No abstract available